Effect of sieved fractionation on the physical, flow and hydration properties of Boscia senegalensis Lam., Dichostachys glomerata Forssk. and Hibiscus sabdariffa L. powders - Deli, Markusse (Food Sci Biotechnol, 2019)
This study aimed at evaluating the effect of successive grinding and sieving processes on the physicochemical properties of powders obtained from Boscia senegalensis seeds, Dichostachys glomerata fruits and Hibiscus sabdariffa calyxes. Plant powders were fractionated into four granulometric classes and their properties were compared to those of unsieved powders. Mean particle size exerted a significant influence (p < 0.05) on the plant powders properties. The smaller the particle size of the powder fraction, the higher the protein, lipid and ash contents and the lower the carbohydrate and fiber contents. The decrease in particle size increased particle sphericity and elongation and enhanced flowability of B. senegalensis and D. glomerata powders, whereas an inverse tendency seemed to be observed for H. sabdariffa powders. Water absorption capacity, water solubility index and dispersibility were improved for finer particles for all plants. Sieve fractionation is a novel approach for improving physicochemical properties of plant powders.